Creative commons for educators and librarians - Creative Commons (Organization) (Chicago : ALA Editions, 2020)
"The authoritative source for learning about using creative commons licenses and advocating for their use in your academic community"--
1 What Is Creative Commons? 1 1.1 The Story of Creative Commons 2 1.2 Creative Commons Today 6 1.3 Additional Resources 9 2 Copyright Law 13 2.1 Copyright Basics 14 2.2 Global Aspects of Copyright 23 2.3 The Public Domain 27 2.4 Exceptions and Limitations of Copyright 31 2.5 Additional Resources 34 3 Anatomy of a CC License 39 3.1 License Design and Terminology 39 3.2 License Scope 45 3.3 License Types 49 3.4 License Enforceability 54 3.5 Additional Resources 59 4 Using CC Licenses and CC-Licensed Works 61 4.1 Choosing and Applying a CC License 61 4.2 Things to Consider after CC Licensing 69 4.3 Finding and Reusing CC-Licensed Work 76 4.4 Remixing CC-Licensed Works 79 4.5 Additional Resources 86 5 Creative Commons for Librarians and Educators 91 5.1 Open Access to Scholarship 92 5.2 Open Pedagogy and Practices 101 5.3 OER, Open Textbooks, Open Courses 104 5.4 Finding, Evaluating, and Adapting Resources 110 5.5 Creating and Sharing OER 118 5.6 Opening Up Your Institution 122 5.7 Additional Resources 126 Index | 131
Includes bibliographical references and index
Keywords: Creative Commons (Organization); Copyright licenses -- United States; Library copyright policies -- United States